Morphology and molecular characterization of Vanda tricolor × Vanda limbata orchid hybrid based on VOH1 gene characters - Alydarafa, Hafshah; Melati, Chrisnanda Ayu; Semiarti, Endang (Universitas Gadjah Mada, 2024)
Vanda is a monopodial epiphyte orchid that spreads throughout Asia and Southeast Asia reaching 70 species. Indonesia itself has its own endemic Vanda orchid such as Vanda tricolor and Vanda limbata. A hybrid of V. tricolor and V. limbata is predicted to form a new specific character in the flower and leaf. The purpose of this study was to determine the morphological and molecular differences between V. tricolor, V. limbata, and Vanda hybrids resulting from crosses between that two orchids, by analysing the morphological characteristics of the roots, leaves, flowers and the structure of the Vanda Orchid Homeobox1 (VOH1) shoot‐forming gene isolated from V. tricolor, V. limbata, and their hybrids. The morphological analysis was conducted using RHS colour chart, size measurement of plants, and the transversal preparation of the leaf. Molecular analysis was performed by PCR using Dendrobium Orchid Homeobox 1 (DOH1) primers, followed by sequencing and bioinformatic analysis. Morphologically, the flower’s colour of the hybrid is most similar to V. limbata but the flower’s patterns are more similar to V. tricolor meanwhile the leaf colour of the hybrid is brighter than the both parents. The slides illustrate the sclerenchyma tissue is made up of strongly thickened walls containing lignin indicates the presence of homeobox DOH1 gene homolog, namely VOH1. The molecular result displayed by the phylogenetic tree of the VOH1 indicates that the hybrid has more similarities with V. limbata.